SENTINEL LYMPH NODE BIOPSY IN TREATMENT OF PENILE CANCER - Vu Dinh, Tam; Nguyen Dinh, Quan; Le Thanh, Hien; Ta Thi Ha, Phuong; Nguyen Huu, Quang; Nguyen Hong, Son; Vu Nguyen, Binh; Nguyen Canh, Tung (Tạp chí Da liễu học Việt Nam, 2024)
Objective: The management of lymph node metastases is crucial in penile cancer surgery. Sentinel lymph node biopsy (SLNB) is a minimally invasive procedure used to assess the presence of lymph node metastasis. The objective is to evaluate the efficiency of SLNB in the treatment of penile cancer. Methods: This retrospective observational study included 31 patients diagnosed with penile cancer who underwent surgery and SLNB at the National Hospital of Dermatology between January 2018 and May 2021. Results: The average age of patients was 58.4 ± 12.3 years old. The majority of patients had a history of phimosis (87.1%) and a treatment delay of over 1 year (67.7%). All 31 patients with penile cancer had squamous cell carcinoma (SCC) as the histological type, with the majority undergoing partial penectomy (87.1%). Out of 61 inguinal regions examined in 31 patients, lymph node metastasis was detected in one region (3.2%). The average follow-up time was 45.2 ± 12.1 months. One SLNB-negative patient was found to have inguinal lymph node metastasis after 12 months, resulting in a false-negative rate of 50%. The complication rate was 8.2%. Conclusion: SLNB utilizing a radioisotope tracer can significantly reduce the incidence and severity of complications associated with inguinal lymph node dissection in patients with penile cancer. Received 25 June 2023 Revised 24 September 2023 Accepted 28 November 2023